Acceleration of the partial element equivalent circuit method with uniform tessellation—Part II: Frequency domain solver with interpolation and reuse of partial elements. (7th December 2017) - Romano, Daniele; Lombardi, Luigi; Antonini, Giulio
Abstract: Stated the importance of accelerating electromagnetic numerical methods to perform accurate and fast virtual prototyping, addressing electromagnetic compatibility/electromagnetic interference issues, in this work, we propose a novel strategy for fast frequency sweeps arising in the partial element equivalent circuit method. Since, as shown in Part I, many geometrical configurations are repeated for a uniform tessellation of 3D structures, the calculation of volume and surface integrals required to fill the partial element matrices can be performed only for a subset of the total elements. Furthermore, since these integrals slowly change with frequency, they can be easily interpolated. Finally, since the interpolation is used over a reduced number of coefficients, their computation can be performed in a vectorialized fashion. All this process leads to an impressive acceleration in the computation of partial elements for the entire frequency sweep by paying a little overhead of random access memory usage. The efficiency and accuracy of the proposed method are demonstrated through its application to 2 pertinent problems.